Hollow Modules With Respect to an Arbitrary Submodule - Al-Bahrani, B. H.; Al-Redeeni , H. S. (Iraqi Journal of Science, 2022)
In this paper ,we introduce hollow modules with respect to an arbitrary submodule .Let M be a non-zero module and T be a submodule of M .We say that M is aT-hollow module if every proper submodule K of M such that T ⊈ K is a T-small submodule of M .We investigate the basic properties of a T-hollow module